Analisis Agilitas Sumber Daya Manusia: Studi Kasus Pada PT Asuransi Kredit Indonesia - Megawaty, Megawaty (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
This study aims to analyse and determine the agility of human resources associated with work-life balance factors and work stress at PT Asuransi Kredit Indonesia. The sampling technique in this study was the snowball sampling technique so that 6 informants were obtained. The method used in this study was a qualitative method with case study data types. Data analysis used the help of the Nvivo application. The results of this study indicate that the concept of HR agility can be observed in various aspects of individual work attitudes and behaviors. First, there is a positive impact on work-life balance if someone is agile at work. Work-life balance which is described as a balance of work that can be completed well but still maintains balance with personal life is achieved in the organization because HR is able to adapt to change and focus on their tasks. Second, work stress has a negative impact on HR agility. High work demands and pressures cause HR to experience work stress, causing them to not be agile at work.